Ideal desiccation periods of Urochloa ruziziensis for a no-till sunflower crop - Giancotti, P. R. F. [UNESP]; Nepomuceno, M. P. [UNESP]; Alves, P. L. C. A. [UNESP]; Yamauti, M. S. [UNESP] (Gorgan Univ Agricultural Sciences &natural Resources, 2015)
Sowing crops following cover crops on forage may cause injuries and productivity reduction, due reasons as allelopathy or glyphosate residues. The objective of this study was to evaluate the influence of differing periods between cover crop (Urochloa ruziziensis) desiccation with glyphosate and sunflower (Aguara 4) sowing in a no-tillage system on crop development and productivity. Two assays were performed in two seasons, one in pots and the other in a field. Treatments in field assay consisted on 5 desiccation times of U. ruziziensis (with an application of glyphosate at 1.08 kg ae ha(-1)) preceding the sowing of no-till sunflower (0, 3, 7, 10 and 30 days). At the pot assays, 6 times were studied: 0, 3, 7, 10, 15 and 20 days between cover crop desiccation and sunflower sowing. A control without cover crop was also included in this assay. Biometric evaluations were performed at the vegetative stage and at harvest. As the period between U. ruziziensis desiccation and sunflower sowing was shortened, achene production in sunflower was exponentially reduced. Glyphosate application at 3 or 0 days pre sowing diminished sunflower development and achene production by approximately 30% compared to desiccation periods greater than 7 days.
Keywords: Glyphosate; Allelopathy; Cover crop